2004
DOI: 10.1039/b409988e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of multiferroic BiFeO3 nanotubes

Abstract: Multiferroic bismuth ferrite (BiFeO(3)) nanotubes have been synthesized using a modified template methodology and characterized by a number of techniques, including XRD, SEM, TEM, HRTEM as well as EDX and SAED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 20 publications
2
75
1
1
Order By: Relevance
“…7 Various procedures have been developed to synthesize BiFeO 3 nanostructure materials such as nanotubes, nanoparticles, and nanospindles. Park et al 8 synthesized the BiFeO 3 nanotubes with alumina template. Han et al 9 reported hydrothermal synthesis of bismuth ferrites with various morphologies.…”
Section: Eco-friendly Catalysis and Energy Laboratory (Nrl) Departmementioning
confidence: 99%
“…7 Various procedures have been developed to synthesize BiFeO 3 nanostructure materials such as nanotubes, nanoparticles, and nanospindles. Park et al 8 synthesized the BiFeO 3 nanotubes with alumina template. Han et al 9 reported hydrothermal synthesis of bismuth ferrites with various morphologies.…”
Section: Eco-friendly Catalysis and Energy Laboratory (Nrl) Departmementioning
confidence: 99%
“…In particular, nanostructured magneto-electric (ME) multiferroic materials with the coexistence of electric and magnetic order parameters are of great scientific and technological interest [1,2,8,[10][11][12][13][14]. Such materials are excellent candidates for electroactive applications and offer a wide opportunity for the development of novel 5 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases these methods seem successful in order to obtain BiFeO 3 nanoparticles [74][75][76][77][78], but divergences are also frequent. Actually it has been suggested that the BiFeO 3 obtained by these wet chemistry routes evidences a metastable behavior and under certain conditions -again contradictory [44,68]-it decomposes leading to secondary phase byproducts.…”
Section: Mixed Oxides Synthesismentioning
confidence: 99%